'Chiral compartmentation' in metabolism: Enzyme stereo‐specificity yielding evolutionary options. Issue 17 (22nd May 2013) - Kuchel, Philip W.; Pagès, Guilhem; Naumann, Christoph
Abstract : The activities of the two lactate‐producing pathways have been described by numerical integration of simultaneous non‐linear differential equations, based on enzyme models like that introduced by Michaelis and Menten in 1913.